1979
DOI: 10.1002/dvg.1020010110
|View full text |Cite
|
Sign up to set email alerts
|

Maternal effect for genes encoding 6‐phosphogluconate dehydrogenase and glucose‐6‐phosphate dehydrogenase in Drosophila melanogaster

Abstract: W e studied the maternal effect for two enzymes of the pentose cycle, 6-phosphogluconate dehydrogenase (6PGD) and glucose-6-phosphate dehydrogenase (G6PD), using a genetic system based on the interaction of Pgd-and Z w -alleles, which inactivate 6PGD and G6PD, respectively. The presence and formation of the enzymes was investigated in those individuals that had not received the corresponding genes from the mother. We revealed maternal forms of the enzymes, detectable up to the pupal stage. The activities of "m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…A comparable situation is reported by Gerasimova and Smirnova (1979) who showed that in the case of 6 phosphogluconate dehydrogenase (6PGD) long-lived stable mRNA was transmitted with the egg cytoplasm and translated during the development of D. melanogaster, leading to large increase of 6PGD activity even in the absence of a functional Pgd gene. However, in the case of ADH this would imply that the rate of synthesis from the maternal mRNA is exactly the same as the rate of degradation of the maternal ADH.…”
Section: Mean Age Of the Eggs At The Transfer To Alcohol Food (Hours)mentioning
confidence: 52%
See 1 more Smart Citation
“…A comparable situation is reported by Gerasimova and Smirnova (1979) who showed that in the case of 6 phosphogluconate dehydrogenase (6PGD) long-lived stable mRNA was transmitted with the egg cytoplasm and translated during the development of D. melanogaster, leading to large increase of 6PGD activity even in the absence of a functional Pgd gene. However, in the case of ADH this would imply that the rate of synthesis from the maternal mRNA is exactly the same as the rate of degradation of the maternal ADH.…”
Section: Mean Age Of the Eggs At The Transfer To Alcohol Food (Hours)mentioning
confidence: 52%
“…The differential survival of Adh-null genotypes is probably caused by maternal effects. Early embryonic development is largely conditioned by the large amount of cytoplasm that contains the products of the maternal genes (Gerasimova and Smirnova, 1979).…”
Section: Mean Age Of the Eggs At The Transfer To Alcohol Food (Hours)mentioning
confidence: 99%
“…The egg cytoplasm of embryos contains proteins and mRNAs from the mother (Gerasimova and Smirnova, 1979). It is known (Wright and Shaw, 1974; Leibenguth et a!., 1979) that in eggs of .…”
Section: Ethanol Concentrat!on(% V/v)mentioning
confidence: 99%